Macroeconomics - Parkin, Michael (Addison-Wesley, 1998)
Parkin’s Macroeconomics is a worldwide leader because it provides a serious, analytical approach to the discipline using the latest policy and data. Parkin trains students to think like economists by offering a clear introduction to theory and applying the concepts to today’s events, news, and research.